Nursing documentation of newborns with birth weight under 1500 g in an Italian Neonatal Intensive Care Unit: a cross-mapping study to develop an ICNP® Subset - Tommasi, Valentina; Bassola, Barbara; Merlo, Chiara; Coscia, Paola; Alessandrini, Marco; Miraglia, Giuseppe; Sessa, Samuele; Cilluffo, Silvia; Lusignani, Maura (Nursing in the 21st Century, 2023)
NURSING DOCUMENTATION OF NEWBORNS WITH BIRTH WEIGHT UNDER 1500 G IN AN ITALIAN NEONATAL INTENSIVE CARE UNIT: A CROSS-MAPPING STUDY TO DEVELOP AN ICNP® SUBSETAim. This study aims to verify the possibility of developing an International Classification for Nursing Practice (ICNP) Subset for preterm newborns hospitalized in Neonatal Intensive Care Unit (NICU).Material and methods. This retrospective descriptive study is a lexical cross-mapping from nurses’ notes to the ICNP. The study analyzes a convenience sample of 115 newborns’ nursing notes of a NICU. The sample included preterm newborns with birth weight under 1500 g hospitalized for at least three days. The frequency distribution, and the percentage frequency distribution of ICNP terms, together with ICNP terms for each need of the Italian nursing conceptual model were calculated.Results. As many as 99.8% of nursing phenomena in nurses’ notes found correspondence with ICNP terms. A total number of 203 ICNP terms described nursing phenomena, of which 161 belonged to pre-coordinated axes. Frequency of ICNP terms was categorized according to an Italian nursing conceptual model. Need of Nutrition and Hydration, need of Breathing and need of Urinary and Bowel Elimination were the patients’ needs with the highest number of ICNP terms.Conclusions. Results of the study suggest the possibility of developing an ICNP Subset for the NICU. Further studies are needed to validate a Subset and new ICNP terms.